2015
DOI: 10.1093/mmy/myv013
|View full text |Cite
|
Sign up to set email alerts
|

MALDI-TOF typing highlights geographical and fluconazole resistance clusters in Candida glabrata

Abstract: Utilizing matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectra for Candida glabrata typing would be a cost-effective and easy-to-use alternative to classical DNA-based typing methods. This study aimed to use MALDI-TOF for the typing of C. glabrata clinical isolates from various geographical origins and test its capacity to differentiate between fluconazole-sensitive and -resistant strains.Both microsatellite length polymorphism (MLP) and MALDI-TOF mass spectra of 58 C. glabrata i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 25 publications
3
21
0
1
Order By: Relevance
“…glabrata populations isolated from patients in Paris and Montpellier, which are 800 km apart, displayed genetic differentiation ( F ST  = 0.11, P  = 0.054). Using the same MLVA scheme as in the present study, Dhieb et al 32. have shown highly significant genetic differentiation ( F ST  = 0.359, P  < 10 −5 ) between C .…”
Section: Discussionsupporting
confidence: 53%
“…glabrata populations isolated from patients in Paris and Montpellier, which are 800 km apart, displayed genetic differentiation ( F ST  = 0.11, P  = 0.054). Using the same MLVA scheme as in the present study, Dhieb et al 32. have shown highly significant genetic differentiation ( F ST  = 0.359, P  < 10 −5 ) between C .…”
Section: Discussionsupporting
confidence: 53%
“…Many studies have likewise found no association between C. glabrata genotypes and antifungal resistance (Dodgson et al, 2003; Abbes et al, 2011). However, Dhieb et al noted that both microsatellite genotypes and MALDI-TOF MS analysis could highlight C. glabrata population structures associated with specific geographic origin or antifungal drug resistance pattern (Dhieb et al, 2015). In our study, we noticed that during 2010–2011 in one hospital (Hospital BD) 80.8% (21/26) C. glabrata isolates were of the same genetic type (ST7 and T25), suggesting possible clonal presence/transmission of C. glabrata .…”
Section: Discussionmentioning
confidence: 99%
“…To date many papers have shown the ability of MALDI-TOF in accurately distinguishing different clusters of Candida strains, geographically grouped as in the case of Candida auris (Pracash et al, 2016) or in the case of multidrug resistant Candida glabrata (Dhieb et al, 2015) and Candida parapsilosis complex (De Carolis et al, 2014). MALDI-TOF mass spectra for genotyping would represent a rapid, first-level, easy, and cost-effective way to support clinicians, during uncommon fungal outbreaks, in treatment decision-making and in a clinical microbiology lab, although only WGS can confirm it.…”
Section: Discussionmentioning
confidence: 99%